An Insight into Male Infertility: A Narrative Review - Jessica Alyas,; Noor Khalid,; Hijab Fatima,; Tayyaba Arif,; Sarah Ishaq,; Sara Chouhadary,; Ayesha Zulfiqar,; Muhamad Usama Azhar,; Shumaila Zulfiqar, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Male infertility is a widespread health issue globally, frequently remaining untreated due to stigmatization and the challenges in diagnosis and treatment. This review presents a comprehensive update on the literature covering key aspects such as causes, diagnostic techniques, and treatment options for managing male factor infertility. It includes an in-depth analysis of global infertility data, using resources from the World Health Organization, Web of Science, Google Scholar, Elsevier, Medline, PubMed, and Scopus databases to gather relevant articles on male infertility. A total of 41 articles from 2000-2023 were reviewed. High throughput techniques, along with sophisticated assays, are being employed for accurate diagnosis. Surgical procedures such as testicular sperm extraction, vasovasostomy, vasoepididymostomy, sperm retrieval techniques, and non-surgical procedures including sclerotherapy, gonadotropin-releasing hormone therapy, and antiestrogens are available to treat infertile males. Additionally, in recent years, flavonoids have been extensively explored for their antioxidant, anti-inflammatory, immune-stimulating, anti-apoptotic, anticarcinogenic, anti-allergic, and antiviral activities. These properties of flavonoids are being investigated for their potential to address biological mechanisms underlying anomalies such as spermatogenesis disturbance and sperm quality decline. This review serves as a comprehensive guide to better understand the etiologies and treatment modalities of male factor infertility, ultimately facilitating affected individuals in making informed reproductive choices.